Context-dependent judgments of color that might allow color constancy in scenes with multiple regions of illumination. - Lee, R; Smithson, H (2012)
For a color-constant observer, a change in the spectral composition of the illumination is accompanied by a corresponding change in the chromaticity associated with an achromatic percept. However, maintaining color constancy for different regions of illumination within a scene implies the maintenance of multiple perceptual references. We investigated the features of a scene that enable the maintenance of separate perceptual references for two displaced but overlapping chromaticity distributions. The time-averaged, retinotopically localized stimulus was the primary determinant of color appearance judgments. However, spatial separation of test samples additionally served as a symbolic cue that allowed observers to maintain two separate perceptual references.